Mengembangkan Model Perencanaan Strategis Kontekstual Berbasis Kearifan Lokal untuk Manajemen Sekolah di Sulawesi Selatan - Mustabsyirah, Mustabsyirah; Abdullah, Fahmi; Fitriah, Maulidyah; Sola, Ermi (Lembaga Yasin AlSys, 2025)
This article develops a Contextual Strategic Planning Model (CSPM) grounded in local wisdom as an effort to enhance the effectiveness of school management in South Sulawesi. The model is driven by persistent challenges in educational planning, such as limited stakeholder participation, resource constraints, and suboptimal evaluation mechanisms, particularly in regions marked by complex socio-cultural dynamics. The study aims to formulate a strategic planning model that is adaptive to local contexts by integrating the cultural values of South Sulawesi. A descriptive qualitative approach was employed through library research, analyzing selected literature from the past four years related to educational strategy and local values. The analysis reveals that incorporating principles of local wisdom, such as Siri’ Na Pacce (dignity, integrity, social responsibility), Sipakatau (mutual respect, justice), and Sipakalebbi (equality, community support) into elements of strategic planning, including vision, mission, strategic objectives, and implementation strategies, can enhance the contextual relevance of education policy. The CSPM contributes to strengthening social cohesion, fostering ethical and responsive learning environments, and transforming schools into resilient ecosystems capable of navigating global disruptions without abandoning cultural roots. Successful implementation of CSPM requires multilevel collaboration among local governments, traditional leaders, schools, and communities; capacity building for educators; development of hybrid evaluation indicators (academic and cultural); and policy advocacy to support the operationalization of culturally grounded strategies. Without sustained commitment and dynamic implementation, the potential of local wisdom risks being reduced to mere normative discourse.